Literature Review of Visit to Visit Lipid Variability as a Predictor of Cardiovascular Events - Aidina Trini Aulia; Nurhikmawati Nurhikmawati; Akina Maulidhany Tahir; Fadillah Maricar; Purwati Pole Rio (Journal La Medihealtico, 2026)
Cardiovascular disease remains a major global health problem due to its substantial contribution to morbidity and mortality. The World Health Organization reports that cardiovascular disease is the leading cause of death worldwide, accounting for approximately 17.9 million deaths each year. In Indonesia, reports from the Ministry of Health show a persistent increase in cardiovascular disease prevalence. Dyslipidemia, defined as an imbalance in blood lipid levels, is a major modifiable risk factor associated with cardiovascular events, making lipid control a key focus of preventive strategies. Visit to visit lipid variability (VLV) refers to fluctuations in lipid parameters such as total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides across different clinical visits over a certain period. Recent studies indicate that higher variability in lipid levels is independently associated with an increased risk of coronary heart disease, stroke, and cardiovascular mortality. This study adopted a literature review design to examine the role of VLV as a predictor of cardiovascular events. Ten national and international journal articles were selected based on predefined inclusion and exclusion criteria. The reviewed evidence consistently shows that high variability in lipid levels, particularly LDL-C and HDL-C, is linked to a greater risk of myocardial infarction, stroke, acute coronary syndrome, and cardiovascular-related death in various populations, including patients with diabetes mellitus and familial hypercholesterolemia. Conversely, maintaining stable lipid levels over time is associated with a reduced risk of adverse cardiovascular outcomes. These findings highlight the importance of continuous lipid monitoring and long-term lipid stability as essential components in efforts to prevent and control cardiovascular disease.